Understanding minority recruitment to the police: beyond systematic review - Fielding, Nigel (Policing and society, 2024)
Recruiting ethnic minority police officers is widely seen as a way to improve police effectiveness and police/public relations, and systematic reviews are often commended as the most robust way to evaluate such policies. We argue that the tenets of classic systematic review are, however, inadequate to that task, and that a more inclusive methodological palette would advance our understanding of this and other important policing policies. Our principal empirical example is a systematic review we conducted that examined whether ethnic minority recruitment has beneficial effects on arrest rates and public satisfaction with police. After evaluating 10,791 studies, eleven satisfied methodological inclusion criteria, but they could not offer conclusive evidence on the effects of minority recruitment on arrest rates or public satisfaction. The example illustrates the obstacles to systematic reviews in contemporary police research. We then profile recent studies that benefit cumulative understanding of the effects of minority recruitment by employing more diverse methodologies, with each study addressing a distinct component that coheres around a logic model.